2004
DOI: 10.1124/jpet.103.064691
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Inhibition of T Helper 1, but Not T Helper 2, Cytokines in Vitro by L-826,141 [4-{2-(3,4-Bisdifluromethoxyphenyl)-2-{4-(1,1,1,3,3,3-hexafluoro-2-hydroxypropan-2-yl)-phenyl]-ethyl}-3-methylpyridine-1-oxide], a Potent and Selective Phosphodiesterase 4 Inhibitor

Abstract: L-826,141 [4-{2-(3,4-bis-difluromethoxyphenyl)-2-{4-(1,1,1, 3,3,3-hexafluoro-2-hydroxypropan-2-yl)-phenyl]-ethyl}-3-methylpyridine-1-oxide] is a selective and potent inhibitor of phosphodiesterase 4 (PDE4) with an IC 50 value of 0.26 to 2.4 nM for inhibition of the catalytic activity of PDE4A, B, C, and D. The cAMP elevation that can be maintained by PDE4 inhibitors attenuates the signaling cascades that lead to the production of certain cytokines. In cellular-based assays, L-826,141 transcriptionally down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 42 publications
1
34
1
Order By: Relevance
“…As summarized by their intrinsic potencies against the multiple recombinant cAMP-PDEs in Table 1, Cpd-A and roflumilast are potent PDE4 inhibitors, with IC 50 values ranging from 0.2 to 2.4 nM and from 0.1 to 0.6 nM for the inhibition of PDE4A, 4B, 4C, and 4D, respectively. Cpd-A and roflumilast are Ͼ400-and 10,000-fold more potent than their weaker PDE3 inhibition, respectively (Claveau et al, 2004). Trequinsin, with IC 50 value of ϳ0.05 nM against PDE3A and 3B, is Ͼ6000-fold more potent compared with its weaker PDE4 inhibition.…”
Section: Pde3 and Pde4 Are The Major Camp-pdes In T84mentioning
confidence: 97%
See 3 more Smart Citations
“…As summarized by their intrinsic potencies against the multiple recombinant cAMP-PDEs in Table 1, Cpd-A and roflumilast are potent PDE4 inhibitors, with IC 50 values ranging from 0.2 to 2.4 nM and from 0.1 to 0.6 nM for the inhibition of PDE4A, 4B, 4C, and 4D, respectively. Cpd-A and roflumilast are Ͼ400-and 10,000-fold more potent than their weaker PDE3 inhibition, respectively (Claveau et al, 2004). Trequinsin, with IC 50 value of ϳ0.05 nM against PDE3A and 3B, is Ͼ6000-fold more potent compared with its weaker PDE4 inhibition.…”
Section: Pde3 and Pde4 Are The Major Camp-pdes In T84mentioning
confidence: 97%
“…Agents such as PDE4 and PDE4D inhibitors that can reduce the exuberant inflammation response and simultaneously enhance mucociliary clearance through CFTR activation in airway may provide additional benefits over antiinflammatory treatment alone in their management. Cpd-A and roflumilast belong to the second generation nonselective PDE4 inhibitors, effectively suppressing the overproduction of leukotrienes and a variety of proinflammatory cytokines in vitro and in animal models (Hatzelmann and Schudt, 2001;Claveau et al, 2004). Treatment with roflumilast at 0.5 mg once daily has significantly improved airway function in asthmatic and COPD patients, with its plasma concentration reached a C max of 3.8 ng/ml (ϳ9.5 nM) and the active N-oxide metabolite being severalfold higher (Reid, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study demonstrated that specific inhibition of PDE4 had no significant effect on Th2 cell-mediated IL-4 or IL-13 generation, but preferentially inhibited Th1 cell cytokine generation (IFN-γ) [52]. PDE4 inhibitors also partially inhibit phytohemagglutinin and anti-CD3/anti-CD28 stimulates the proliferation of CD4+ and CD8+ T cells [21,53]. A separate study demonstrated that dual PDE4A/B and PDE4D inhibitors inhibited antigen-stimulated human T cell proliferation, with mean IC 50 values significantly correlating with compound potency against the catalytic activity of recombinant PDE4A or PDE4B, but not with the catalytic activity of recombinant PDE4D [43].…”
Section: Effects Of Selective Pde Inhibitors On Airway Smooth Musclementioning
confidence: 99%